2018
DOI: 10.1111/trf.14995
|View full text |Cite
|
Sign up to set email alerts
|

A rationale for universal tranexamic acid in major joint arthroplasty: overall efficacy and impact of risk factors for transfusion

Abstract: BACKGROUND Tranexamic acid (TXA) therapy is effective in reducing postoperative red blood cell (RBC) transfusion in total joint arthroplasty (TJA), yet uncertainty persists regarding comparative efficacy and safety among specific patient subgroups. We assessed the impact of a universal TXA protocol on RBC transfusion, postoperative hemoglobin (Hb), and adverse outcomes to determine whether TXA is safe and effective in TJA, both overall and in clinically relevant subgroups. STUDY DESIGN AND METHODS A retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Consistent with the report of Althoff et al, 10 the benefit of using multiple PBM measures in a patient is demonstrated in Figure 3. As reported previously, the use of TXA in patients undergoing cardiac, 11 orthopedic, [12][13][14] and gynecological surgeries 15,16 has been associated with positive outcomes, including a reduction in transfusions. In the ONTraC program, utilization of TXA increased from about 32% in 2011 to >90% in 2021 for orthopedic patients undergoing elective total joint arthroplasty.…”
Section: What Have We Been Able To Achieve?mentioning
confidence: 73%
“…Consistent with the report of Althoff et al, 10 the benefit of using multiple PBM measures in a patient is demonstrated in Figure 3. As reported previously, the use of TXA in patients undergoing cardiac, 11 orthopedic, [12][13][14] and gynecological surgeries 15,16 has been associated with positive outcomes, including a reduction in transfusions. In the ONTraC program, utilization of TXA increased from about 32% in 2011 to >90% in 2021 for orthopedic patients undergoing elective total joint arthroplasty.…”
Section: What Have We Been Able To Achieve?mentioning
confidence: 73%
“…Elective, urgent, and emergent orthopedic surgery is associated with significant blood loss, and RBC transfusion, providing the rationale for broad utilization of PBM measures including perioperative TXA use. 13 The results of small randomized-controlled trials, as well as subsequent systematic reviews and meta-analyses, demonstrate that perioperative TXA is effective at reducing surgical blood loss and allogeneic transfusion in orthopedic surgery. [97][98][99][100] A recent retrospective analysis assessed prophylactic TXA use in noncardiac surgeries at high risk for blood transfusion in 14,300 patients between 2014 and 2016.…”
Section: Txa In Orthopedic Surgerymentioning
confidence: 99%
“…97,102 The use of TXA, as a component of PBM, has been strongly advocated for, and compliance with TXA administration has reached as high as 95% of elective patients in some centers. 13 TXA use for elective long bone procedures and repair of bone fractures has undergone several investigations. 99,103,104 Patients with acute fractures differ from elective patients in that they usually face urgent/emergent surgery and may have increased risks associated with thrombosis.…”
Section: Txa In Orthopedic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In my hospital, we have implemented universal intravenous tranexamic acid administration in arthroplasty. This initiative led to a significant reduction in RBC transfusion rate and resulted in higher postoperative haemoglobin values [28].…”
Section: Perioperative Use Of Tranexamic Acidmentioning
confidence: 99%